2019
DOI: 10.5194/acp-19-3905-2019
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of trace gases, PM, and aerosol optical properties during the 2017 NW US wildfire smoke event

Abstract: Abstract. In mid-August through mid-September of 2017 a major wildfire smoke and haze episode strongly impacted most of the NW US and SW Canada. During this period our ground-based site in Missoula, Montana, experienced heavy smoke impacts for ∼ 500 h (up to 471 µg m−3 hourly average PM2.5). We measured wildfire trace gases, PM2.5 (particulate matter ≤2.5 µm in diameter), and black carbon and submicron aerosol scattering and absorption at 870 and 401 nm. This may be the most extensive real-time data for these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 111 publications
15
67
0
Order By: Relevance
“…In the size range of our samples, backscatter ratios and scattering Angstrom exponents decrease with particle size (Selimovic et al, 2019). An anti-correlation between these intensive parameters and MSE is expected and is observed (Figs.…”
Section: Observationssupporting
confidence: 62%
See 1 more Smart Citation
“…In the size range of our samples, backscatter ratios and scattering Angstrom exponents decrease with particle size (Selimovic et al, 2019). An anti-correlation between these intensive parameters and MSE is expected and is observed (Figs.…”
Section: Observationssupporting
confidence: 62%
“…On a global basis, wildfire aerosols are estimated to have a net direct radiative effect of 0.17 watts m -2 , 1-σ uncertainty = -0.45 -+0.15 W m -2 (Bond et al, 2013) The rapid evolution of aerosol optical properties of fresh smoke contributes to the radiative effect uncertainty (Yokelson et al, 2009;Akagi et al, 2012;May et al, 2015;Vakkari et al, 2018;Selimovic et al, 2019). In this study we are concerned with 35 changes in wildfire optical properties that occur in the near-field, extending from the time it takes a smoke plume to rise to aircraft-sampling altitude to circa three hours downwind.…”
Section: Introductionmentioning
confidence: 99%
“…Forrister et al 2015 collected filter samples in the plumes of wildfires with different transport times during the SEAC4RS campaign, and found that the BrC absorbance lifetime at 370 nm was 9-15 hours. Similarly, Selimovic et al 2019 found a significant decrease in AAE 420 after 10 hours of daytime aging during a wildfire event in the Northwestern US. Sumlin et al, 2017 aged smoldering peat BBOA in an OFR, and reported a decrease of ~40-50% in the aerosol mass absorption coefficients at 375 nm and 405 nm after 4.5 equivalent aging days.…”
Section: Aging By Condensed-phase Photolysismentioning
confidence: 82%
“…In 20 view of the importance of the number concentrations of aerosol particles, especially cloud condensation nuclei, for climate change, it is unfortunate that there have only been a few additional measurements of their emission factors in the last two decades. Another climate-relevant component, for which we have no emission data at this time, is brown carbon (Andreae and Gelencsér, 2006), which has been shown to account for about half of the aerosol light absorption by biomass smoke at 401 nm (Selimovic et al, 2019) and 25-45 % at 550 nm (Tian et al, 2019). 25…”
Section: Emission Factors For Chemical Species From the Various Combumentioning
confidence: 99%